Pengaruh Persepsi Riba dan Bunga Bank terhadap Minat Menabung di Lembaga Keuangan Syariah pada Masyarakat Pesantren - Anwar, Muhammad Khoirul; Baratullah, Braham Maya (Quranomic: Jurnal Ekonomi dan Bisnis Islam, 2023)
The purpose of this study is to determine the influence of the perception of usury and bank interest on the interest in saving in shari'a financial institutions in the pesantren community which is carried out at the An-Nur Ngrukem Islamic boarding school, Pendowoharjo, Sewon, Bantul, Yogyakarta. This type of research is quantitative research whose sampling method uses the Non-Probability Sampling method using one of the techniques in it, namely Purposive Sampling or can be called Judgemental Sampling. The data collection technique used a questionnaire conducted on 78 respondents. Normality test using Kolmogorov-Smirnov analysis. The data analysis technique uses a coefficient of determination test (R2), a t test, and an f test, using the help of SPSS version 25 software. The results of the study showed the influence of the perception of usury and the perception of bank interest on the interest in saving in shari'a financial institutions in the pesantren community. This is based on the findings of the data processing results which show a positive relationship and have a significant effect of 26.0%.